In vivo characterization of four (18)F-labeled S1PR1 tracers for neuroinflammation - Liu, Hui (Mol Imaging Biol, 2020)
PURPOSE: The sphingosine-1-phosphate receptor 1 (S1PR1) is an important biomarker for imaging inflammation in the central nervous system (CNS). Herein we report our recent evaluation of four (18)F-labeled S1PR1 tracers ((18)F-TZ43113, (18)F-TZ35104, (18)F-TZ4877, and (18)F-TZ4881) in a rat model of multiple sclerosis (MS). PROCEDURES: MicroPET studies of each tracer’s uptake and kinetics were performed in the experimental autoimmune encephalomyelitis (EAE) rat model of MS to quantify upregulated S1PR1 expression in the lumbar spinal cord of EAE rats. Western blot analysis was conducted to confirm the differences in the expression of S1PR1 protein level in EAE and sham rats. Radiometabolite analysis was performed for the most promising candidate in rats. RESULTS: All four S1PR1 tracers detected increased S1PR1 levels in response to neuroinflammation in the lumbar spinal cord of EAE rats, which was supported by western blot results. The ranked order of tracer uptake in rat spinal cord was (18)F-TZ4877>(18)F-TZ4881>(18)F-TZ35104>(18)F-TZ43113. (18)F-TZ4877 had the highest uptake of the four tracers and showed good kinetic modeling fits in rat spinal cord using an image-based method of arterial blood input function. Radiometabolite analysis of (18)F-TZ4877 showed good in vivo stability with no major radiometabolite accumulation in the brain. CONCLUSION: Among these four new PET tracers, (18)F-TZ4877 showed the most favorable profile for assessing S1PR1 expression in the EAE rat model of MS. Further characterization of these radiotracers in other models of neuroinflammation is warranted to identify a promising (18)F-labeled tracer for imaging S1PR1 in vivo.